Microstructure and mechanical properties of A7N01 aluminum alloy weld joints filled with ER5356 and ER5087 weld wires - Xie H.; Hu L.; Ma Q.-H.; Meng W.; Yin X.-H. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2022)
The A7N01-T5 aluminum alloy plates with the thickness of 12 mm were welded with the ER5356 and ER5087 welding wires, respectively, by the method of Metal Inert Gas (MIG) welding. The mechanical properties and microstructures of the welded joints were investigated by micro-hardness measurement, tensile test, energy dispersive spectroscopy (EDS), electron backscattered diffraction (EBSD) and transmission electron microscopy (TEM). The results showed that the tensile strength and elongation of 7N01/5087 welded joint (the 7N01 aluminum alloy plate welded with ER5087 wire) were greater than those of 7N01/5356 welded joint (the 7N01 aluminum alloy plate welded with ER5356 wires), respectively. The high strength and the good elongation of 7N01/5087 welded joint were mainly attributed to the microstructure refinement in the weld zone through adding Zr element to promote the nucleation of Al grains around the Al3Zr sites.